THE EFFECT OF ONLINE-BASED EDUCATION ON TREATMENT ATTITUDES AND MEDICATION ADHERENCE OF TUBERCULOSIS PATIENTS AT THE DENPASAR CITY HEALTH CENTER - Ni Made Andrinia Ratih Sri Indraswari; Ida Ayu Manik Partha Sutema; I Made Bakta (Journal Pharmaceutical Science and Application, 2022)
Background: Tuberculosis is an infectious disease with a high prevalence rate in Denpasar City. Medication adherence affects increased tuberculosis cases in Denpasar City. Medication adherence in tuberculosis patients is associated with a low attitude toward treatment, so it is necessary to make efforts to improve treatment attitudes and medication adherence of tuberculosis patients by providing health education. Online-based education with Google Meet can be a solution in delivering health education with virtual face-to-face features, so education delivery becomes more effective. Objective: This study aims to determine the effect of online-based education on treatment attitudes and medication adherence of tuberculosis patients at the Denpasar City Health Center. Methods: The pre-experiment study used one group pretest-posttest design that was conducted from February until April 2022 at several public health centers in Denpasar City. The total samples of 30 tuberculosis patients accorded the inclusion criteria were taken by purposive sampling. A questionnaire was used to measure treatment attitudes, where online-based education is given a week after the pre-test and the post-test is given 2 weeks after online-based education. Pill-count method was used to measure medication adherence. Wilcoxon analysis was used to analyze research data. Results: Wilcoxon's analysis showed a significant increase in treatment attitudes and medication adherence of tuberculosis patients before and after online-based education with google meet (p<0.05). Conclusion: Online-based education with google meet provides an increase in treatment attitudes and medication adherence of tuberculosis patients at the Denpasar City Health Center. Keywords: Online-based Education; Treatment Attitudes; Medication Adherence; Tuberculosis